Data4Ag: Using data to transform smallholder farming - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2019)
Digitalisation of agriculture is driving an exponential growth in the amount of data on agriculture being collected. This calls for new tools and approaches to gather, manage, analyse and use this data. CTA’s project, Data4Ag: Agricultural data systems to transform smallholder farming, focuses on transforming smallholder agriculture through the use of data management by agri-enterprises.